Investigation of the role of morphology on the magnetic properties of Ca2Mn3O8 materials. Issue 41 (2nd October 2017) - Vera Stimpson, Laura J.; Ramos, Silvia; Stenning, Gavin B. G.; Jura, Marek; Parry, Stephen; Cibin, Giannantonio; Arnold, Donna C.
Abstract : Ca2 Mn3 O8 exhibits a complex 'bow-tie' magnetic lattice resulting in interesting magnetic behaviour. Abstract : Ca2 Mn3 O8 exhibits a complex layered structure comprised of Mn3 O8 4− layers separated by Ca 2+ ions. In contrast with the more traditional triangular delafossite layered materials the Mn3 O8 4− layers additionally exhibit an ordered vacancy, which forms a 'bow-tie' like arrangement of the Mn 4+ ions. We report a comprehensive study of the magnetic properties of a series of Ca2 Mn3 O8 materials with different morphologies. EXAFS and XANES analysis confirm no differences in either manganese environment or oxidation state between materials. Apparent differences in magnetic order from SQUID magnetometry can be rationalised by uncompensated surface spins arising as a result of changes to the surface to volume ratio between morphologies. Furthermore, these data suggest these materials are potentially frustrated in nature, due to the triangular connectivity of Mn 4+ spins, with a simple 'spin-up/spin-down' (↑↓) antiferromagnetic model unable to explain the data collected.